New Qmaths 11A - Brodie, Ross and Swift, Stephen (South Melbourne Cengage Learning, 2008)
"Maths textbook for Queensland year 11 students."--Provided by publisher.
Includes Colored Illustrations and Index.
Keywords: Mathematics -- Textbooks